Interactive effects of weaning age and creep feed on the performance of sows and their piglets - BALAMURALIKRISHNAN, B; PARK, J H; KIM, I H (The Indian Journal of Animal Sciences, 2017)
The study was conducted to determine the interactive effects of creep feed and different weaning age of piglets on the production performance of lactating sows and performances of piglets. Our study indicated that the piglets provided with creep feed led to a higher BW, ADG at nursery and weaned pigs, and also significant difference on ADFI during nursery phase. Different weaning age had increased ADFI and G:F ratio in pre- and post-weaned pigs.Interactions between creep feed and weaning age had significant difference on growth performances among nursery and weaned pigs. Furthermore, the obtained data suggested that the inclusion of creep feed with increased weaning age may reduce the estrus interval in sows and improve the growth performance of piglet during lactation and postweaning.